Intermedial Performance and Politics in the Public Sphere (Avant-Gardes in Performance, 2018)
This volume is a collection of scholarly articles and interviews with intermedial artists working with the concepts of public sphere at the intersection of aesthetics and politics. It explores the response of socially-engaged artistic practices to the current crisis in politics and media. It also critically examines urgent issues such as rampant nationalism and populism, expanding neoliberalism, the refugee crisis, growing inosculations of corporate and cyber culture, and the ongoing geopolitical changes in the Middle East. Can intermedial performances reflect the present artistic and political dilemmas in Europe and beyond? The collection provides theoretical frameworks that interrogate the role that spectators as citizens can play in our mediatized world while focusing on the functions of immersion, participation, and civic engagement in contemporary performance and society. The collection provides analyses by international scholars from Europe, Asia, and the USA, covering global performance created in the twenty-first century. It also introduces interviews with internationally acclaimed intermedial artists and companies such as BERLIN, Rimini Protokoll, Dries Verhoeven, Akira Takayama, and Kris Verdonck.